you need x when g(x) = 55
x^2+6x=55
x^2+6x-55 = 0
(x+11)(x-5) = 0
Since the domain is x >= -3, that means that
g^-1(55) = 5
Note that specifying that x >= -3 means we have chosen only one branch of the parabola, whose vertex is at (-3,-9).
Since g(x) = x^2+6x,
x = -3 ±√(g+9)
we choose to use only the
x = -3+√(g+9)
Thus, when g=55, x=-3+√64 = -3+8 = 5
If
g(x) = x2 + 6x
with
x ≥ −3,
find
g−1(55)
I need help solving this problem this is an example but it does not thoroughly is explained. :/
1 answer